Neurocognitive development : disorders and disabilities - Gallagher, Anne (Neuropsychologist); Bulteau, Christine; Cohen, David, 1964-; Michaud, Jacques L. (Handbook of clinical neurology, 2020)
"This is one volume of a two-volume work on neurocognitive development, focusing separately on normative and non-normative development. The disorders and disabilities volume focuses on disorders of intellectual abilities, language, learning memory as well as psychiatric developmental disorders. The developmental aspects of neurological diseases in children is also covered. Chapters discuss when and how these disorders develop, the genetics and neurophysiology of their operation, and their evaluation and assessment in clinical practice. Assessment, treatment, and long-term outcome are provided as well as advances in methods and tools for assessment"--Publisher's description